Diet of American Kestrel (Falco sparverius Linnaeus, 1758) in two localities at the north ecuadorian interandean valley - Pozo-Zamora, Glenda M. (2017)
We present the diet of American Kestrel Falco sparverius, through pellets analysis, from two different localities in the Ecuadorian north-interandean region. The most representative prey items from Sangolquí and Tababela were Coleoptera (48.4, and 39.5%), followed by Orthoptera (31.3 and 30.7%), respectively. In terms of biomass, mammals were the most important food resource in both sites, the invasive rodent Mus musculus was the most preferred prey; it would provide an appreciable predatory as pest control service. The Shannon index (H'= 1.894) indicates a median diversity of prey and, a diet amplitude of 0.26 suggests that the American Kestrel in our study sites is a specialist. Its diet differs from its relatives from other habitats where they present a generalist diet.